School Belonging: A Review of the History, Current Trends, and Future Directions. (24th June 2016) - Slaten, Christopher D.; Ferguson, Jonathan K.; Allen, Kelly-Ann; Brodrick, Dianne-Vella; Waters, Lea
Abstract : School belonging, at both a school and university level, has been well documented as a predictor of academic and psychosocial success. The construct has been examined by scholars in a variety of different professional disciplines (e.g., education, psychology, sociology) and continues to be consistently researched. Although significant contributions have been made in the field, there are still additional areas of investigation needed, as well as interventions that need to be designed and explored. The current article was designed to review the theoretical foundations of belonging, conceptualise school belonging with respect to how it is presented in the literature, discuss the key variables related to school belonging, present a summary of the predictors of school belonging, discuss school belonging in a university setting, and posit future directions for research.